Antenna Pointing to the Geo Satellite Using Converted NORAD TLE from Osculating Orbital Elements - Byoung-Sun Lee; Hae-Yeon Kim; Yoola Hwang; Jaehoon Kim (Journal of Astronomy and Space Sciences, 2007)
Antenna pointing analysis for a geostationary satellite has been performed for using the NORAD Two-Line-Elements (TLE) converted from osculating Keplerian orbital elements. In order to check the possibility of the reception of the satellite signal, the antenna offset angles have been derived for the Communications, Ocean, and Meteorological Satellite (COMS) which carries out weekly East-West and North-South station-keeping maneuvers and twice a day thruster assisted momentum dumping. Throughout the analysis, it is shown that the use of converted NORAD TLE simplifies the antenna pointing related interfaces in satellite mission control system. For a highly eccentric transfer orbit cases, further analysis presents that the converted NORAD TLE from near apogee gives more favorable results.